Quantifying sustainable development the future of tropical economies - Hall. Charles, A. S.; Perez, Carlos Leon; Leclerc, Gregoire
Until recently, the phenomenal economic development of the Asian tigers, Chile, and Malaysia, as well as the sustained economic growth of the United States, painted a very desirable and optimistic picture of free markets, fiscal responsibility, and, more generally, the entire dogma of neoclassical economics. As of the fall of 1998, however, the economies of many tropical countries have contracted severely, and the enthusiasm of the developing tropics for the free market and all of its ancillary policies is decidedly cooler. Have our traditional approaches to economics been failing the developi.